The business web genre: a genre analysis on the websites of selected Malaysian small - Mohd Johari, Muhammad Danish; Mohd Ali, Afida (Springer, 2015)
Websites are another form of service provided to the public to help improve information sharing of a particular discourse community. Selection of a website is influenced by the persuasiveness of the website’s content. As the power of the Internet grows, so do the opportunities for small businesses. In fact, the Internet is already contributing 4.1 % a year to Malaysia’s economy, and that’s set to rise even more over the next 3 years. With the upsurge of E-entrepreneurs in Malaysia, business websites demonstrate a variety of styles in web writing and design, indicating a creative yet bold sense of marketing and advertising of products and services. Hence, the purpose of this study was to establish the common moves and steps found in a corpus of selected Malaysian SME business websites. This study used Swales (Genre analysis: English in academic and research settings. Cambridge University Press, Cambridge, 1990) CARS model and the two-dimensional genre model (Askehave and Nielsen, Proc 38th Hawaii Int Conf Syst Sci 00(C):1–8, 2005) to analyse the data. The study has revealed that there are obligatory and optional moves in the business web genre. The goal of this genre is to inform and to promote the company’s product and services via its website. Findings from this study may be a good resource for students and practitioners to design and write for the web.